EVALUASI PENYUSUNAN LAPORAN KEUANGAN PADA TOKO DAILY LIFE STORE BERDASARKAN SAK EMKM - Heriyanto3, Diana Auliya Rahman1 Mardiana2 (EKONOMIA, 2021)
The purpose of this research is to know and evaluate the recognition, measurement, presentation, and application in the financial statements of the Daily Life Store. In accordance with the objectives of this study, the subject matter put forward